2021
DOI: 10.1097/scs.0000000000008274
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Degree of Nasal Septum Deviation With Sinonasal Structures and Variations

Abstract: We aimed to evaluate whether the nasal septum deviation affects the development of sinonasal structures. Patients who had undergone paranasal sinus computed tomography (PNS-CT) imaging due to nasal obstruction were divided into 3 groups according to the septal deviation angle; group I: 0°to 9°, group II: 10°to 15°, and group III: > 15°. The features of sinonasal structures were recorded when evaluating PNS-CT. There were totally 234 patients, 119 patients in group I, 68 in group II, and 47 in group III. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Other authors found correlations between the development of chronic sinusitis and anatomical anomalies in the nose: concha bullosa, ager nasi cells, Haller cells and NSD 4,[10][11][12]17,18 . Atsal et al noted that the frequency of these nasal anomalies increases with an increasing angle of deviation of the nasal septum from the midline 19 . Although on the other hand, there are opinions that since NSD affects 44-80% of the population, it is more accurate to talk about the coexistence of NSD with chronic rhinitis [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors found correlations between the development of chronic sinusitis and anatomical anomalies in the nose: concha bullosa, ager nasi cells, Haller cells and NSD 4,[10][11][12]17,18 . Atsal et al noted that the frequency of these nasal anomalies increases with an increasing angle of deviation of the nasal septum from the midline 19 . Although on the other hand, there are opinions that since NSD affects 44-80% of the population, it is more accurate to talk about the coexistence of NSD with chronic rhinitis [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%